......... ...... Как то так
Пошаговое объяснение:
1)Приводим к общему знаменателю
13/1 - 5/9=
13*9/9 - 5/9 =
117/9 - 5/9 = 112/9=
112/9=12 4/9
ответ:12 4/9
2)Целое умножаем на знаменатель
26 1/8 + 6/8=(26*8 +1)/8 +6/8=
(208+1)/8 +6/8 =209/8 +6/8=
215/8=26 7/8
3)Вычитаем из целого
8-2/ 7=7 7/ 7-2/ 7=
7 5/7
......... ...... Как то так
Пошаговое объяснение:
1)Приводим к общему знаменателю
13/1 - 5/9=
13*9/9 - 5/9 =
117/9 - 5/9 = 112/9=
112/9=12 4/9
ответ:12 4/9
2)Целое умножаем на знаменатель
26 1/8 + 6/8=(26*8 +1)/8 +6/8=
(208+1)/8 +6/8 =209/8 +6/8=
215/8=26 7/8
3)Вычитаем из целого
8-2/ 7=7 7/ 7-2/ 7=
7 5/7